Energy partitioning over a semi‐arid shrubland in northern China. Issue 6 (15th October 2015) - Jia, X.; Zha, T. S.; Gong, J. N.; Wu, B.; Zhang, Y. Q.; Qin, S. G.; Chen, G. P.; Feng, W.; Kellomäki, S.; Peltola, H.
Abstract: During the last decade, the widely distributed shrublands in northern China have shown significant signs of recovery from desertification, the result of widespread conservation practices. However, to support the current efforts in conservation, more knowledge is needed on surface energy partitioning and its biophysical controls. Using eddy‐covariance measurements made over a semi‐arid shrubland in northwest China in 2012, we examined how surface energy‐balance components vary on diurnal and seasonal scales, and how biophysical factors control bulk surface parameters and energy exchange. Sensible heat flux ( H ) exceeded latent heat flux ( λE ) during most of the year, resulting in an annual Bowen ratio ( β, i.e. H / λE ) of 2.0. λE exceeded H only in mid‐summer when frequent rainfall co‐occurred with the seasonal peak in leaf area index ( LAI ). Evapotranspiration reached a daily maximum of 3.3 mm day −1, and summed to 283 mm yr −1 . The evaporative fraction ( EF, i.e. λE / Rn ), Priestley–Taylor coefficient ( α ), surface conductance ( gs ) and decoupling coefficient ( Ω ) were all positively correlated with soil water content ( SWC ) and LAI . The direct enhancement of λE by high vapour pressure deficit ( VPD ) was buffered by a concurrent suppression of gs . The gs played a direct role in controlling EF and α by mediating the effects of LAI, SWC and VPD . Our results highlight the importance of adaptive plant responses to water scarcity in regulating ecosystem energy partitioning, and suggest an important role for revegetation in the reversal of desertification in semi‐arid areas. Copyright © 2015 John Wiley & Sons, Ltd.